Retrospective Study of Facial Fractures - Kaura, Sameer (Ann Maxillofac Surg, 2018)
AIM: The aim of this study was to give an insight into the retrospective analysis of a number of maxillofacial trauma cases reported to our institute and research center. MATERIALS AND METHODS: The data for this study was obtained from the medical records and outpatient prescription slips of cases treated at the Oral and Maxillofacial Surgery Department from 2010 to 2016. Etiology, age, gender, pattern of fracture, and surgical treatment modalities undertaken in these patients were recorded. RESULTS: A total of 353 maxillofacial trauma patients with mean age of 40 years, treated at our institute were evaluated from 2010 to 2016. Mandible was the most commonly fractured bone with parasymphysis as the most frequent site. Majority of victims were males (male:female ratio of 4:1) and also in the third decade of life. This study showed that 73% patients were treated by open reduction and internal fixation (ORIF), 25.8% by intermaxillary fixation (IMF) and Stabilization of fracture mandible with acrylic splint and circummandibular wiring was done in 0.8% pediatric patients. CONCLUSION: It was concluded that road traffic accidents were reported as the leading cause of maxillofacial fractures followed by assault, falls, and familial dispute. Maxillofacial surgeons as health care providers must continue their ‘face it’ campaign to decrease the incidence of road traffic accidents. Open reduction and internal fixation remains the gold standard treatment modality.